Teaching literacy to learners with dyslexia a multisensory approach - Kelly, Kathleen S.; Phillips, Sylvia (Los Angeles SAGE, 2016)
The second edition of this bestselling book provides a structured multi-sensory programme for teaching literacy to children and young people from 5-18 with dyslexia and other specific literacy difficulties. Supported by a wealth of resources available online and updated throughout, the new edition now includes a brand new section on Implementing the Accelerated Programme for learners who have already acquired some literacy skills. This includes: A placement test to indicate whether the programme is appropriate ; A diagnostic assessment procedure to determine where the learner should begin on the Accelerated Programme ; Examples of lesson plans, reading cards and spelling cards to help teachers prepare resources for their students. With tried and tested strategies and activities this book continues to provide everything you need to help improve and develop the literacy skills of learners in your setting including: the rationale for a structured multi-sensory approach ; the development of phonological, reading, writing and spelling skills ; working with learners who have English as an Additional Language (EAL) ; lesson structure and lesson-planning ; alphabet and dictionary skills ; memory work and study skills ; teaching the programme to groups ; ideas for working with young children. -- Provided by publisher.
Part I: Teaching learners with dyslexia: theory and context -- Chapter 1: The contribution of theories of causation to the development of a multisensory teaching programme -- Chapter 2: The role of memory in acquiring literacy skills -- Chapter 3: Phonological skills, literacy and dyslexia -- Chapter 4: The development of reading skills -- Chapter 5: Spelling development and dyslexia -- Chapter 6: Teaching handwriting -- Chapter 7: Dyslexia and learners for whom English is an additional language -- Part II: Conquering literacy: a multi sensory programme for teaching learners with dyslexia, teaching strategies -- Chapter 8: Principles, teaching strategies, and programme structure -- Chapter 9: Lesson planning -- Chapter 10: Alphabet and dictionary work -- Chapter 11: Introducing the new teaching point in a lesson -- Chapter 12: The role of memory in the programme -- Chapter 13: Study skills within the programme -- Part III: Conquering Literacy - A multisensory programme -- The conquering literacy programme: examples of activities.
Includes bibliographical references and indexes.
Keywords: Dyslexic children -- Education -- Great Britain; Literacy -- Study and teaching -- Great Britain; English language -- Study and teaching -- Great Britain; Learning disabled children -- Education -- Great Britain; Literacy -- Study and teaching -- Activity programs; English language -- Study and teaching -- Activity programs